Best Practice in Poverty Analysis : Malawi Human Resources and Poverty - Profile and Priorities for Action, November 1995 - World Bank (Washington, DC, 2012)
The report requested by the government of Malawi updates the poverty assessment completed in March 1990. It will guide policy and investment priorities, and inform the design of programs intended to improve living conditions and increase incomes of the people in Malawi. A greater understanding of the magnitude and the profile of poverty will also make it easier to implement a monitoring system to evaluate the effects of programs and track the progress of key indicators of poverty. The profile confirms that the level of human resource development in Malawi is dismal and that poverty is widespread and severe. Health and education indicators in Malawi are among the worst in the world. Strategies to reduce poverty in Malawi will require substantial efforts in every sector.